2015
DOI: 10.7314/apjcp.2015.16.3.1289
|View full text |Cite
|
Sign up to set email alerts
|

Anal Papanicolaou Smear in Women with Abnormal Cytology: a Thai Hospital Experience

Abstract: Background: Anal intraepithelial lesions (AIL) are likely to represent a precursor for anal cancer. Women infected with human immunodeficiency virus (HIV) may be at higher risk of anal cancer but a screening program for AIL still is not routinely recommended. We here studied the relationship of dysplastic cells from cervical and anal cytology in HIV-infected women. Materials and Methods: This prospective study was conducted in Prapokklao Hospital, Thailand during 2013-2014. Five hundred and ninety nine HIV-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 18 publications
3
17
0
Order By: Relevance
“…Although 34% of specimens were inadequate for evaluation in a previous study of anal Pap tests in HIV-infected women, 8 adequacy in our study was similar to that reported in a group of mostly HIV-negative men who have sex with men. In addition, fewer inadequate specimens were noted with provider-performed anal specimen collection.…”
supporting
confidence: 83%
“…Although 34% of specimens were inadequate for evaluation in a previous study of anal Pap tests in HIV-infected women, 8 adequacy in our study was similar to that reported in a group of mostly HIV-negative men who have sex with men. In addition, fewer inadequate specimens were noted with provider-performed anal specimen collection.…”
supporting
confidence: 83%
“…Moreover, this method is relatively easy in interpretation. When concerned about cervical cancer screening, Pap test is widely accepted as an effective screening tool for cervical precancerous lesions and cancer [15]. However, there is still no definite grading recommendation offered for oral cytological changes which may progress to cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to lack of interest in oral cytology or the high rate of false results caused by inadequate sampling procedures, low cellularity or variation in technical quality [14]. In settlement with our approach, a previous study adapted Papanicolaou smears to categorize anal intraepithelial lesions using Bethesda System Terminology [15]. In this study, we have demonstrated that about 38.6% of petrol station workers exhibit buccal cytological changes ranging from ASC-US to HSIL, which are approved to be precancerous changes in accordance with the Bethesda System Terminology applied for cervical epithelial lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations